Room on the broom - Donaldson, Julia; Scheffler, Axel (New York : Puffin Books, 2003)
A witch finds room on her broom for all the animals that ask for a ride, and they repay her kindness by rescuing her from a dragon.
Booklist, September 2001.
Bulletin (Center for Children's books), September 2001.
Kirkus Review, August 2001.
Publisher's Weekly, September 2001.
School Library Journal, September 2001.
3.7.
Keywords: Animals -- Fiction; Dragons -- Fiction; Stories in rhyme; Witches -- Fiction